2019
DOI: 10.1002/jbm.a.36617
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of macrophage phenotype via phagocytosis of drug‐loaded microparticles

Abstract: Monocyte‐derived macrophages play a critical role in directing wound pathology following injury. Depending on their phenotype, macrophages also promote tissue regeneration. However, the therapeutic administration of macrophages with a controlled phenotype is challenging because macrophages are highly plastic and quickly revert to a detrimental, inflammatory phenotype in response to the environment of a damaged tissue. To address this issue, we developed a novel strategy to modulate macrophage phenotype intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 51 publications
(101 reference statements)
1
31
0
Order By: Relevance
“…[ 44 ] PLGA particles have also been used in several studies for engineering M ϕ s as therapeutic carriers. [ 45 ] For example, DOX‐loaded PLGA NPs with a diameter of about 141 nm, polydispersity index (PdI) of 0.086, and zeta potential of −31.7 mV were prepared and incubated with the M ϕ s for 2 h. As a result of tumor‐targeting efficiency, DOX accumulation and penetration into the tumor microenvironment of nude mice bearing intracranial U87 glioma was higher when the drug incorporated NPs were loaded into M ϕ s. [ 45b ] A similar study used a biomimetic DDS composed of DOX‐loaded PLGA NPs, incorporated within M1 M ϕ s for glioma treatment (DOX‐PLGA‐M1). [ 45c ] PLGA NPs, with an average size of 156.9 ± 7.1 nm and a loading efficiency of 4.35 ± 0.56% for DOX, were incubated with the M1 M ϕ s that had a higher NP‐loading capacity as compared to the M0 M ϕ s. The final concentration of DOX in the M ϕ s was 34 ± 2.3 µg per 5 × 10 6 M ϕ s and PLGA NPs were localized in the lysosomal compartment in the M1 cells.…”
Section: Ex Vivo Manipulated Alive Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 44 ] PLGA particles have also been used in several studies for engineering M ϕ s as therapeutic carriers. [ 45 ] For example, DOX‐loaded PLGA NPs with a diameter of about 141 nm, polydispersity index (PdI) of 0.086, and zeta potential of −31.7 mV were prepared and incubated with the M ϕ s for 2 h. As a result of tumor‐targeting efficiency, DOX accumulation and penetration into the tumor microenvironment of nude mice bearing intracranial U87 glioma was higher when the drug incorporated NPs were loaded into M ϕ s. [ 45b ] A similar study used a biomimetic DDS composed of DOX‐loaded PLGA NPs, incorporated within M1 M ϕ s for glioma treatment (DOX‐PLGA‐M1). [ 45c ] PLGA NPs, with an average size of 156.9 ± 7.1 nm and a loading efficiency of 4.35 ± 0.56% for DOX, were incubated with the M1 M ϕ s that had a higher NP‐loading capacity as compared to the M0 M ϕ s. The final concentration of DOX in the M ϕ s was 34 ± 2.3 µg per 5 × 10 6 M ϕ s and PLGA NPs were localized in the lysosomal compartment in the M1 cells.…”
Section: Ex Vivo Manipulated Alive Immune Cellsmentioning
confidence: 99%
“…utilizing magnetic NPs accompanied by an external magnetic field. [ 45d ] To speed up the migration of drug‐PLGA NP‐M ϕ s to the tumor site, they reported incorporating DTX and spherical 10 nm size Fe 3 O 4 NPs within spherical PLGA NPs with a mean final diameter of 300 nm, followed by loading them into M ϕ s with incubation ( Figure a). Fluorescent imaging revealed uptake of NPs by the M ϕ s (Figure 4b).…”
Section: Ex Vivo Manipulated Alive Immune Cellsmentioning
confidence: 99%
“… 278 Notably, dexamethasone-loaded PLGA microparticles were utilized to polarize macrophages toward an anti-inflammatory phenotype and resulted in a significant suppression of pro-inflammatory genes and TNF-α secretion. 279 , 280 All of these methods may be viable options to deliver these anti-inflammatory agents, especially if they can be formulated and delivered directly to the lungs to reduce or preclude systemic immunosuppression that may result in worse outcomes for patients treated with corticosteroids.…”
Section: Biomaterials and Particle-based Immune Engineering Opportunimentioning
confidence: 99%
“…For proof of concept, we utilized the anti-inflammatory glucocorticoid dexamethasone (Dex) because it down-regulates transcription of inflammatory cytokines [24][25][26][27] and simultaneously enhances functions associated with regeneration such as homing [27][28][29] , phagocytosis 24,26,27,30,31 , and iron regulation 27,32,33 within macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Selective delivery of Dex to the monocyte/macrophage population could hold promising therapeutic advantages by avoiding these off-target effects. Previously, we showed that Dex-loaded microparticles could downregulate inflammatory gene expression of primary human macrophages under non-inflammatory conditions in vitro 26,27 . Within this study, we analyzed the ability of the microparticles to release drug intracellularly for several weeks and to maintain macrophage phenotype in the presence of inflammatory stimuli for one week in vitro.…”
Section: Introductionmentioning
confidence: 99%